Effect of different concentrations of fertilizer salts on the primary production of hydroponic green fodder in maize (Zea mays L.) in San Carlos, Costa Rica - Barquero, Vinicio (2019)
Green hydroponic forage (GHF) consists in the germination of seeds using only water and nutrients, with efficient biomass production in small spaces and in short periods of time for animal fed. In order to know the effect of different concentrations of salts on the production of dry matter of maize FVH, an experiment was conducted under a completely randomized design, in the Controlled Environment Laboratoryof the Technological Institute of Costa Rica, San Carlos Technological Campus. Three concentrations of electrical conductivities (EC) (0.5 μS, 1 μS and 2 μS) were tested from a mixture of four fertilizer salts (calcium nitrate, potassium nitrate, monopotassium phosphate and magnesium sulfate) and a control (drinking water without fertilizing salts, 0 μS). The results showed that treatments with ≥1 μS had significantly higher values in fresh weight, percentage of dry matter and plant height, although without statistical differences in dry matter, root length and number of leaves. The values obtained allowed the development of a prediction equation for dry weight based on fresh weight.